2016
DOI: 10.1093/gbe/evw095
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Signatures of Speciation in Sympatric and Allopatric Hawaiian Picture-WingedDrosophila

Abstract: The Hawaiian archipelago provides a natural arena for understanding adaptive radiation and speciation. The Hawaiian Drosophila are one of the most diverse endemic groups in Hawaiì with up to 1,000 species. We sequenced and analyzed entire genomes of recently diverged species of Hawaiian picture-winged Drosophila, Drosophila silvestris and Drosophila heteroneura from Hawaiì Island, in comparison with Drosophila planitibia, their sister species from Maui, a neighboring island where a common ancestor of all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…However, allopatric divergence may also be affected by adaptive processes (e.g., local adaptation 55,56 ), which might lead to genomic islands of divergence 57,58 . Distinguishing between these possibilities requires a large number of genetic markers that can be mapped across the genome 59,60 . Although our analysis only included a few individuals per population and a reduced representation of the species’ genome (285 SNPs), the high number of fixed loci between populations, and the broad distribution of these loci across the majority of the species’ chromosomes, is consistent with a model of strict allopatric divergence 38,53 .…”
Section: Discussionmentioning
confidence: 99%
“…However, allopatric divergence may also be affected by adaptive processes (e.g., local adaptation 55,56 ), which might lead to genomic islands of divergence 57,58 . Distinguishing between these possibilities requires a large number of genetic markers that can be mapped across the genome 59,60 . Although our analysis only included a few individuals per population and a reduced representation of the species’ genome (285 SNPs), the high number of fixed loci between populations, and the broad distribution of these loci across the majority of the species’ chromosomes, is consistent with a model of strict allopatric divergence 38,53 .…”
Section: Discussionmentioning
confidence: 99%
“…With the advantage of genomic characterization via high-throughput sequencing combined with recent developments in statistical methods, investigators can now, for nearly any species of interest, estimate parameters to describe the demographic aspects of speciation history with unprecedented resolution (Ellegren et al, 2012;Ellegren, 2014;Gaither et al, 2015;Malinsky et al, 2015;Gante et al, 2016;Kang et al, 2016;Schmitz et al, 2016;Toews et al, 2016;Berner & Roesti, 2017). These aspects are collectively often referred to as the Isolation-with-Migration (IM) model and provide critical information on the rates, direction and possibly timing of gene flow, divergence times (which should be co-estimated with gene flow) and population size trajectories.…”
Section: Box 1: Continuedmentioning
confidence: 99%
“…For example, using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas-9 to create specific mutations in different species backgrounds, Ding et al (2016) identified a gene important for male courtship song (described in detail in New Approaches to Determine the Genetic Basis of Reproductive Isolation). Whole-genome sequencing studies are providing high-resolution analysis of population differentiation and interpopulation gene flow, which have been used to understand the evolutionary history of closely related species and to determine which regions of the genome may contain genes important for speciation (Garrigan et al 2012;Kang et al 2016). Ultimately, these tools and resources will help answer two of the major outstanding questions in speciation: (1) what are the selective forces that contribute to divergence between populations, and 2what is the genetic basis of traits contributing to reproductive isolation.…”
Section: Contents Continuedmentioning
confidence: 99%
“…Going forward, population genomic approaches can be used with the a priori expectation that regions of low gene flow or high differentiation may contain genes for reproductive isolation. In the sister pair D. silvestris and D. heteroneura, Kang et al (2016) sequenced many genomes of each species looking at patterns of differentiation (Fst and dxy) and selection (McDonald-Kreitman tests) to identify candidate loci contributing to reproductive isolation. A major caveat to this approach is that highly differentiated regions may also be consequences of adaptation or genome rearrangements.…”
Section: The Biological Species Concept Genic View Of Speciation Anmentioning
confidence: 99%